2017
DOI: 10.1016/j.jtcvs.2017.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Favorable late survival after aortic surgery under straight deep hypothermic circulatory arrest

Abstract: Aortic surgery with DHCA can be performed with favorable late survival, with the duration of DHCA period having only a limited impact. However, these results cannot be generalized for very long durations of DHCA (>50 minutes), when perfusion methods may be preferable. In elective, nondissection first-time surgeries, a late survival comparable to that in a reference population can be achieved. Early survival is adversely affected by aortic dissection, redo status, and disease extent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Therapeutic hypothermia is used to treat patients experiencing out of hospital cardiac arrest, during pediatric resuscitation, and is commonly used during cardiac surgical procedures (as a means of cerebral protection) involving interruption of blood flow to the brain . Physiologic effects of hypothermia are manifold, including a significant reduction in the tissue's metabolic rate for oxygen and glucose . Although the effects of hypothermia have been well‐established clinically, the mechanisms of its action remain elusive in many tissues, and specifically in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therapeutic hypothermia is used to treat patients experiencing out of hospital cardiac arrest, during pediatric resuscitation, and is commonly used during cardiac surgical procedures (as a means of cerebral protection) involving interruption of blood flow to the brain . Physiologic effects of hypothermia are manifold, including a significant reduction in the tissue's metabolic rate for oxygen and glucose . Although the effects of hypothermia have been well‐established clinically, the mechanisms of its action remain elusive in many tissues, and specifically in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…16 Physiologic effects of hypothermia are manifold, including a significant reduction in the tissue's metabolic rate for oxygen and glucose. 17,18 Although the effects of hypothermia have been well-established clinically, the mechanisms of its action remain elusive in many tissues, and specifically in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 is based on a study (1) conducted many years ago on Dr. Stanley Crawford's patients, which showed that after 40 minutes of circulatory arrest, but with deep hypothermia alone, the risk of stroke increased. More recent studies support that 40 minutes of circulatory arrest is the maximum (2). If a procedure can be completed in less than 25-30 minutes, with hypothermia less than 20 ℃ on nasopharyngeal measurement, then this can be safely done.…”
Section: Reviewmentioning
confidence: 99%
“…In this issue of the Journal, Damberg and colleagues 1 report their experience with straight deep hypothermic circulatory arrest (DHCA) as the sole means of brain protection during operations on the aortic arch in 613 consecutive patients, focusing on late outcomes. 1 The independent variables associated with increased 1-year mortality were acute type A aortic dissection, reoperative status, and the presence of descending thoracic aortic pathology. The independent variables associated with increased mortality beyond 1 year were increased age, postoperative complications (stroke, dialysis, pulmonary complications), and postoperative atrial fibrillation.…”
Section: Nicholas T Kouchoukos MDmentioning
confidence: 99%